Review on using Region of interest for HEVC - Kokare, Parmeshwar; MasoodhuBanu. N.M, Dr (International Journal of Engineering and Technology, 2018)
High efficiency video coding (HEVC) is the latest video compression standard. The coding efficiency of HEVC is 50% more than the preceding standard Advanced video coding (AVC). HEVC has gained this by introducing many advanced techniques such as adaptive block partitioning system known as quadtree, tiles for parallelization, improved entropy coding called Context-Adaptive Binary Arithmetic Coding (CABAC), 35 intra prediction modes (IPMs), etc. all these techniques have increased the complexity of encoding process due to which real time application of HEVC for video transfer is not yet convenient. The main objective of this paper is to provide a review of the recent developments in HEVC, particularly focusing on using region of interest (ROI) for reducing the encoding process time. Summaries of the different approaches to identify the ROI are discussed and a new method is explained.Â